Development of Scale to Measure Attitude of Animal Husbandry Personnel towards using ICAR-IVRI Crystoscope - Kumar, S. P. Sunil; Singh, B. P.; Chander, Mahesh; Suman, Ram Singh (Indian Journal of Extension Education, 2021)
The attitude of animal husbandry personnel toward any animal husbandry technology is an important factor in evaluating the technology and will also aid in the development of future innovative technologies. Based on Likert’s summative rating technique of scale development, a scale was constructed in the year 2020 to measure the attitude of animalhusbandry personnel toward using the ICAR-IVRI Crystoscope. The scale consisted of final 16 statements, including 8 positive and 8 negative statements. Reliability of the scale was calculated using Cronbach’s alpha method which was found to be 0.824 and reflects the high reliability of the measuring instrument. The validity of the scale was tested by expert’s judgment. The reliability and validity of the scale indicate its consistency and precision of the results. This scale can be used to measure the attitude of animal husbandry personnel in similar situation beyond the study area with suitable modifications.